Sports education learning program evaluation in senior high school - Sulistyawati Sulistyawati; Guntur Guntur (Psychology, Evaluation, and Technology in Educational Research, 2019)
The Sports Education learning program evaluation has not been completely implemented. In relation to the statement, the study aims at evaluating the Sports Education learning program in Senior High School degree. Within the conduct of the study, the evaluation involved the CIPP model. Then, the informants for the study consisted of principals, vice principals, 2 Sports Education teachers and 10 students from each of Grade X, Grade XI and Grade XII. The data were gathered by means of interview, observation and documentation. For the data analysis technique, the researcher adopted the descriptive qualitative analysis. The results of the assessment in the study show that the results of context evaluation have already contained the Core Competence and the Basic Competence from 2013 Curriculum. The Components of Input have been good and the learning process of Soccer has been well-performing. Furthermore, the Components of Output show that the mean score of Core Competence 1 and Core Competence 2 belong to the â€œGoodâ€ category, Core Competence 3 belongs to the â€œVery Goodâ€ category (82.24) and Core Competence 4 belongs to the â€œGoodâ€ category (80.50). Therefore, it might be concluded that the Sports Education learning program in Senior High School has been well implemented. Thus, it is recommended that the Sports Education learning program should be continued with several revisions on the process.